Hubungan Gaya Kognitif Dan Motivasi Berprestasi Dengan Hasil Belajar PAI - Prasetiya, Benny; Hidayah, Ulil; Dirgayunita, Aries (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The purpose of this correlational study to determine the relationship of cognitive style and achievement motivation with learning outcomes PAI. The research data was sourced from the test results of cognitive style and tests of achievement motivation and learning outcomes PAI obtained from Value report cards. No results showed a significant relationship between cognitive style with PAI learning outcomes. There is a significant relationship between achievement motivation with learning outcomes PAI. Cognitive style and achievement motivation are jointly associated with learning outcomes PAI